Optimizing a rotor‐stator filter matrix for high‐gradient magnetic separation of functionalized magnetic particles. Issue 5 (25th April 2016) - Shaikh, Yonas S.; Seibert, Christian; Schumann, Christiane; Ferner, Marvin J.; Raddatz, Heike; Kampeis, Percy
Abstract : The processing of wines with enzymes is a process chain in which losses of biocatalyst are unavoidable. A promising technique for the minimization of these losses and for the reduction of processing time is the high‐gradient magnetic separation in combination with enzymes, which are immobilized onto functionalized magnetic particles. When magnetizable particles are used and magnetic separation is applied to separate these particles from nonmagnetizable particles and solutes, the enzymes can be recycled and used for several production batches. The magnetic filter used in this study had a filter matrix with concentrically stacked circular rotor and stator plates which are arranged in an alternating order. Different geometries of the filter plate notches were examined to optimize the reproducibility of particle retention. In computational fluid dynamic studies, the influence of the notch geometries on the shear rate generation was analyzed for the rinsing procedure. Separation experiments with an optimized geometry of the filter plates were carried out in water and white wine suspensions.